LABELLING DAN GUILT BY ASSOCIATION TERHADAP KELUARGA TERPIDANA TERORIS DI INDONESIA: PERSPEKTIF VIKTIMOLOGI TERHADAP VIKTIMISASI (Lex Jurnalica, 2023)
AbstractThe war on terrorism that took place in Indonesia after the 2002 Bali Bombing not only resulted in the victimization of the direct perpetrators of terrorism but also of the families of the perpetrators. Not all of the perpetrators' families also participated in the crime of terrorism. Thus, not a few families of perpetrators of terrorism have also become indirect victims of terrorism. Victimization of the families of perpetrators of criminal acts of terrorism is in the form of labeling and guilt by association. Among the reasons is they have blood relations or are married to the perpetrators of terrorism. This article discusses the labeling and guilt by association of several families of perpetrators of terrorism in Indonesia. The author conducted field research between 2013 – 2018 in several locations in Indonesia. The findings from this study are families of perpetrators of terrorism also experience victimization in the form of labeling and guilt by association. Keywords: victimization; labelling; association; terrorist family Abstrak Perang melawan terorisme yang terjadi di Indonesia pasca Bom Bali 2002 tidak saja melahirkan viktimisasi terhadap pelaku langsung terorisme namun juga terhadap keluarga pelaku. Padahal, tidak semua keluarga pelaku adalah juga turut melakukan tindak pidana terorisme. Maka, tidak sedikit keluarga pelaku terorisme adalah juga telah menjadi korban tidak langsung dari terorisme. Semata-mata karena mereka memiliki hubungan darah ataupun terikat secara perkawinan dengan sang pelaku terorisme. Viktimisasi terhadap keluarga pelaku tindak pidana terorisme adalah dalam bentuk labelling dan guilt by association. Artikel ini membahas tentang labelling dan guilt by association terhadap beberapa keluarga pelaku terorisme di Indonesia. Penelitian lapangan dilakukan antara tahun 2013 – 2018 di beberapa lokasi di Indonesia. Temuan dari penelitian ini adalah keluarga pelaku terorisme adalah juga mengalami viktimisasi dalam bentuk labelling dan guilt by association. Kata kunci : viktimisasi; labelling; association; keluarga pelaku terorisme